The influence of epidural anaesthesia on femoral overlap and Norberg angle in the hip joint of young dysplastic dogs - Vandekerckhove, P. M. F. P.; Janssens, L. A. A.; Ballieu, B. C. W. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
A retrospective study of 61 dogs that underwent triple pelvic osteotomy evaluated the effect of the epidural anaesthesia on the hip laxity as measured by the femoral overlap and Norberg angle before and after epidural anaesthesia. Both the femoral overlap and the Norberg angle measured on the non-operated hip decreased significantly after epidural anaesthesia. (p < 0.0001 and p < 0.001, respectively).
Keywords: Hip dysplasia; joint laxity; epidural anaesthesia